HDAC1 suppresses radiotherapy sensitivity in cervical cancer via regulating HIF-1α/VEGF signaling pathway: HDAC1 suppresses CC through HIF-1α/VEGF - Liu, Li; Gu, Ke; Hua, Dong (Cellular and Molecular Biology, 2023)
Cervical cancer (CC) is the fourth most common cancer amongst females worldwide. Histone deacetylase (HDAC) 1 plays a vital role in several tumors. Nevertheless, its potential and mechanism in radiotherapy sensitivity underlying CC remains obscure. Hence, the objective of this research was to probe the potential of HDAC1 in CC radiotherapy sensitivity and its mechanism of action. The expression HDACs and survival analysis of HDAC1 were investigated based on the GEPIA database. Immunohistochemical staining was implemented to detect HDAC1 and Ki-67 expression in tumor tissues. RT-qPCR and Western blot were conducted to assess HDAC1, HIF-1α, VEGFA, along with VEGFR expressions in CC cells and tumor tissues. Cell viability, apoptosis, invasion, migration, along with cell cycle were analyzed by functional assays. Tumor-bearing nude mice model was established, and the tumor weight and volume were determined. HDAC1 was high-expressed in the tumor tissue and CC cells. In vitro, overexpression of HDAC1 suppressed radiotherapy sensitivity in C33A cells, while knockdown of HDAC1 promoted radiotherapy sensitivity in SiHa cells. In vivo, we found that HDAC1 silence hindered tumor growth and cell proliferation and promoted tumor cell apoptosis in nude mice after radiotherapy. In addition, we found that HDAC1 impacted radiotherapy sensitivity by modulating the HIF-1α/VEGF signaling pathway. In conclusion, HDAC1 suppressed the radiotherapy sensitivity of CC via regulating HIF-1α/VEGF signaling pathway, suggesting that HDAC1 may act as a crucial participant in regulating CC radiosensitivity, which may provide a novel method for treating CC.